Geological evidence for AD 1008 tsunami along the Kachchh coast, Western India: Implications for hazard along the Makran Subduction Zone. Issue 1 (December 2018) - Prizomwala, S.; Gandhi, Drasti; Bhatt, Nilesh; Winkler, Wilfried; Kumar, M.; Makwana, Nisarg; Bhatt, Nishith
Abstract The 2004 Sumatra-Andaman tsunami emphasized the catastrophic nature of such disasters and exposed our knowledge gap of the historical and palaeo events. In the aftermath of this deadly event, the thrust in palaeotsunami studies was restricted to areas in the Indian Ocean, affected by this tsunami. The northern Arabian Sea, which hosts a similar tsunamigenic source i.e. the Makran Subduction Zone (MSZ), has so far remained 'Terra-Incognita '. Here, for the first time, we report geological evidence of the 1008 AD tsunami, also mentioned as 'an enigma ' in the historical reports, by identifying a >250 km long sand sheet with a landward extent of more than 250 m from the Indian coastline. Detailed sedimentology and geochemistry reveals an offshore origin of this sand sheet, from where it was eroded by a high energy wave and deposited in a supratidal environment. Optical and AMS14 C chronology constrains its age of deposition around 1000 AD. The shear size of the sand sheet, laterally and across the coast, along with grain size, a characteristically different provenance, are some of the major indicators, which can be useful in palaeotsunami/palaeostorm deposit distinction. Our report of the AD 1008 event from the Indian coastline, also supports the claim that the Western MSZ, albeit at longer intervals, has experienced major thrust earthquakes (M w > 8) in the historical past. The proximity of this sand sheet to the shoreline does not discount the role of extremely unlikely, large storms as its causal mechanism.